Cetirizine a histamine H1 receptor antagonist improves viral myocarditis - Yamamoto Kanjo; Matsumori Akira; Shimada Miho (BMC, 2010)
Abstract Background We showed that mast cells played a critical role in the progression of heart failure induced by pressure overload and viral myocarditis in mice. In this study, we investigated the effect of cetirizine, a selective H1 receptor antagonist, on experimental viral myocarditis induced by encephalomyocarditis (EMC) virus. Methods Four-week-old inbred male DBA/2 mice were inoculated intraperitoneally with 10 plaque-forming units (pfu) of the EMC virus. Cetirizine was administered orally at a dose of 1 or 10 mg/kg per day for the survival study, and 1 mg/kg for the histologic and gene expression studies, beginning on the day of viral inoculation. Results Cetirizine improved survival dose dependently. Heart weight to body weight ratio was significantly decreased in mice treated with cetirizine. The area of myocardial necrosis was significantly smaller in the hearts of mice treated with cetirizine compared with controls. Gene expressions of tumor necrosis factor, interleukin 6, and metalloproteinase 2 were significantly suppressed in the hearts of mice treated with cetirizine. Conclusion These results suggest that cetirizine exerts its beneficial effects on viral myocarditis by suppressing expression of pro-inflammatory cytokines, genes related to cardiac remodeling in the hearts of mice.